GREEK TERMINOLOGY MEANING THERAPEUTIC AND SURGICAL METHODS OF TREATMENT. GREEK AND LATIN DUPLICATED NAMES (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article discusses the meaning of Greek and Latin terms in therapeutic and surgical disease designations, methods of application, forms of anatomical and clinical doublets in Greek and Latin.